GOOD CORPORATE GOVERNANCE, AUDIT QUALITY, DAN FIRM PERFORMANCE - Maria Natalia; Jovian Samuel (Universitas Muhammadiyah Tangerang, 2019)
This study aims to examine the effect of good corporate governance and audit quality towards firm performance. In addition, this study also examines whether the effect of good corporate governance towards firm performance can be moderated by audit quality variables. Measurement of good corporate governance scores uses ASEAN CG Scorecard, while quality audits are proxied by audit fees and firm rotation audits. Firm performance variables are measured using Tobin's q, ROE, and ROA. The data used in this study is secondary data which is obtained from the annual report of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016. Data analysis method used in this study is multiple linear regression tests. The result shows that good corporate governance and audit quality which are proxied by audit fees has the effect towards the firm performance. This study also succeeded in proving that audit quality can moderate the effect of good corporate governance towards firm performance. Keywords: good corporate governance, audit quality, firm performance, ASEAN CG Scorecard